Pengaruh Dana Alokasi Umum (Dau), Dana Alokasi Khusus (Dak) Dan Pendapatan Asli Daerah (Pad) Terhadap Belanja Daerah Di Diy & Jateng (Studi Kasus Pemerintah Daerah Kabupaten/Kota Di Diy Dan Jateng Tahun 2009-2013) - Trisnawati, Natalie; Adhivinna, Vidya Vitta (Akmenika, 2015)
This research is intended to know the influence of the General Allocation Fund (DAU) Special Allocation Fund (DAK) and Local Own-Source revenue (PAD) of the local expenditure. The sample used in this study were 40 Regency/City in DIY and Central Java sourced from the website of the Financial Department of the Republic Indonesia (www.djpk.kemenkeu.go.id) from the years 2009-2013. The analysis technique used is multiple linear regression test. The test results showed that the General Allocation Fund (DAU) significantly influence of regional expenditure, while the Special Allocation Fund (DAK)) and Local Own-Source revenue (PAD) does not significantly influence the regional expenditure.